Ownership and financial structure of biotechnology SMEs: Evidence from Finland - Raine Hermans; Antti-Jussi Tahavainen (The Research Institute of the Finnish Economy (ETLA), 2002)
The aim of this study is to depict the ownership and financial structure of Finnish small and medium-sized biotechnology enterprises. Most of the firms are owned by several groups of owners. In small companies the largest share of equity is held by individuals active in the business. Private venture capitalist companies own the largest stakes in both large and infant companies, while the same holds for public venture capitalists in adolescent companies and other non-financial firms in middle-aged companies. The low profits in the Finnish biotechnology company, and hence the low level of equity was offset by raising high amounts of capital loans. The governmental institutions Tekes and Sitra are the largest capital loan suppliers. The debt ratio was 25% out of the total assets of the Finnish biotechnology firms. Trade credit, domestic banks and Tekes were the main sources of the debt finance.Principal component analysis shows that equity investments from private venture capital (VC) companies were related to the loans from domestic, both private and public, financial institutions. This raises questions on monitoring aspects of investors. The high equity share of principal owners with significant influence in the board and the high equity share of individuals active in the business seems to keep public investments relatively moderate in the company. The high equity shares of private and public VCs are partially connected to high growth prospects of companies. In order to explain these relations it would be necessary to investigate any systematical features behind the anticipations. – biotechnology ; corporate finance ; financial structure ; ownership structure ; venture capita – – Tutkimuksen tavoitteena on kuvata suomalaisten pienten ja keskisuurten biotekniikkayritysten omistajuus- ja rahoitusrakenteita. Useimmilla yrityksillä on monia omistajaryhmiä. Liiketoiminnassa aktiivisesti mukana toimivat yksityishenkilöt omistavat suurimman osan pienistä biotekniikka-alan pk-yrityksistä. Yksityiset pääomasijoitusyhtiöt omistavat suurimman osuuden sekä suurista että nuorimmista yrityksistä. Julkiset pääomasijoitusinstituutiot omistavat suurimman osan kasvuikäisistä yrityksistä ja muut ei-rahoitusalan yritykset keskiikäisistä yrityksistä. Suomen biotekniikkayritysten alhaiset voitot, ja täten myös oman pääoman tasearvon alentuminen, kompensoitiin ottamalla huomattavia määriä pääomalainaa. Julkiset instituutiot, Tekes ja Sitra ovat suurimmat pääomalainan tarjoajat. Velkaantumisaste oli 25 prosenttia suomalaisten biotekniikka-alan pk-yritysten rahoituksen kokonaisarvosta. Ostovelat muille yrityksille, kotimaiset pankit ja Tekes olivat lainarahoituksen päälähteitä. Pääkomponenttianalyysi osoittaa, että yksityisten pääomasijoitusyhtiöiden omistusosuus oli yhteydessä kotimaisten, sekä yksityisten että julkisten, rahoitusinstituutioiden lainanantoon. Tämä nostaa esiin kysymyksiä sijoittajien monitorointitavoista. Julkisten instituutioiden sijoitukset näyttävät pysyvän joiltain osin vähäisenä sellaisissa yrityksissä, joiden vaikutusvaltaiset pääomistajat tai liiketoimintaan osallistuvat yksityishenkilöt omistavat suuren osan yrityksestä. Yksityisten ja julkisten pääomasijoitusinstituutioiden omistusosuus näyttää liittyvän osittain yritysten suuriin kasvuodotuksiin, minkä selvittämiseksi olisi tarpeellista tutkia odotusten taustalla olevia systemaattisia piirteitä.l – bioteknologia ; yritysrahoitus ; rahoitusrakenne ; omistajuusrakenne ; pääomasijoittaminen
Keywords: 330; Biotechnologie; Unternehmensfinanzierung; Eigentümerstruktur; Risikokapital; Finnland